Policy Strategies to Increase Motor Vehicle Tax Revenue to Support Regional Development in Lampung Province - Makhmudi, Catur (CV. Tripe Konsultan, 2025)
The Provincial Government of Lampung faces significant challenges in increasing its Regional Own-Source Revenue, one of which is through the Motor Vehicle Tax sector. Despite the continuous growth in the number of vehicles, taxpayer compliance remains very low, ranging only between 30–38%. This situation directly affects the region's fiscal capacity to fund development and public services. This policy paper examines the underlying causes of low PKB revenue and formulates data-driven policy recommendations based on field surveys and public policy theories. The data analysis employs a qualitative descriptive approach. Survey results reveal that 86 percent of taxpayers encounter obstacles when paying taxes, such as long queues at Samsat offices or disruptions in the online payment system. Additionally, 44 percent of taxpayers perceive the tax payment procedures to be overly complicated. The analysis indicates that the core issue is the low compliance rate among motor vehicle taxpayers, primarily due to limited access to payment services caused by uneven digital infrastructure and restricted service hours. These factors have significantly contributed to the low PKB revenue in Lampung Province. This policy paper adopts the New Public Management (NPM) approach and the principles of Good Governance by promoting the integrated digitalization of PKB payment services through mobile and web-based applications. Furthermore, extending service hours into the evenings and weekends is recommended to provide greater time flexibility for the public. As a concrete step, it is recommended that the Provincial Government of Lampung issue a new Governor Regulation outlining the technical aspects of PKB services, including coordination among the Regional Revenue Agency, Samsat, the police department, and financial institutions. This initiative is expected to significantly enhance tax compliance, strengthen PAD, and support more autonomous and sustainable regional development.